Leading Teams #7: Adjourning - Sarah A. Bush; Carrie N. Baker; Laura L. Greenhaw (EDIS)
As a part of the Leading Teams series, this article reviews the fifth and final stage of group development: the adjourning stage. An overview of recommendations for performance evaluations and rewards systems is provided. Additionally, the importance of investing time in the adjourning stage and ways to start a new project after the completion of the original team project are described. Written by Sarah A. Bush, Carrie N. Baker, and Laura L. Greenhaw, and published by the UF/IFAS Department of Agricultural Education and Communication, June 2025.